Codex rules OK! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Developing countries should find it easier to participate in the work of the Commission of the Codex Alimentarius thanks to a t36 million fund launched in February 2003 by the FAO and the World Health Organization (WHO).